2014
DOI: 10.1021/jf501644t
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Antioxidant Activity and Functional Components of the Ethanol Extract of Lotus (Nelumbo nucifera) from Various Growing Regions

Abstract: The variations in antioxidant activity and concentration of functional components in the ethanol extracts of lotus seeds and rhizomes based on the growing region and dryness were investigated. Free radical scavenging activity, total phenolic and flavonoid content, and concentration of several specific flavonoids and alkaloids in the ethanol extracts of lotus were measured. Antioxidant activity and its correlative total phenolic content varied characteristically depending on the growing region and dryness. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 43 publications
3
41
0
Order By: Relevance
“…The phytoconstituents of seed and seedpod of Nelumbo nucifera with their medicinal activities are shown in (Tables 3 and 4). 30 in their study had proved that the seedpod of Nelumbo nucifera possessed high levels of phytonutrients when compared to other parts of the plant which well correlated with our study and they were reported for various biological activities such as antioxidant, antiviral, antibacterial, antiinflammatory and cardioprotective activities. In a previous study by Moustafa et al, 31 have shown that the seeds of Nelumbo nucifera possessed thirty eight compounds, but in our study we obtained only fourteen compounds.…”
Section: Resultssupporting
confidence: 91%
“…The phytoconstituents of seed and seedpod of Nelumbo nucifera with their medicinal activities are shown in (Tables 3 and 4). 30 in their study had proved that the seedpod of Nelumbo nucifera possessed high levels of phytonutrients when compared to other parts of the plant which well correlated with our study and they were reported for various biological activities such as antioxidant, antiviral, antibacterial, antiinflammatory and cardioprotective activities. In a previous study by Moustafa et al, 31 have shown that the seeds of Nelumbo nucifera possessed thirty eight compounds, but in our study we obtained only fourteen compounds.…”
Section: Resultssupporting
confidence: 91%
“…In particular, lotus rhizome contains several biological active compounds such as polyphenolic compounds (kaempferol, quercetin, and isoquercetin) and oligomeric procyanidines. In addition, it contains abundant dietary fiber consisting of non-carbohydrate components (Moro et al , 2013; Zhao et al , 2014). Moreover, lotus rhizome has been reported to have multiple physiological efficacies, including anti-inflammatory, antioxidaive, and anti-hypercholesterolemia activities (Hu and Skibsted, 2002; Lee et al , 2006; Tsuruta et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There are not enough data to explain why the fermentation of the lotus tuber was stable, but some hypotheses can be proposed. (a) The substrates contained in the soluble fraction themselves might be slowly fermentable, or (b) certain chemical compounds in lotus tuber, e.g., phytochemicals (Zhao et al, ) and viscous substances, perhaps acidic polysaccharides (Fuchigami & Kishigami, ) might modify the ruminal fermentation. If the latter function helps stabilize the ruminal fermentation, the lotus tuber can be expected to be a substitute for the ionophore antibiotics.…”
Section: Discussionmentioning
confidence: 99%